Lo sport come motore di inclusione sociale: la rete del “calcio solidale” a Roma - Folco Cimagalli (Culture e Studi del Sociale)
Sport is a multidimensional phenomenon, able not only to urge the individual dimension, but also to promote social relationship. For this reason, it is a tool that can promote social inclusion of disadvantaged people who, through sport, are able to run their asset of social relations. The paper focuses on the case of “Fondazione Roma Solidale”. The Foundation is a body part by the City of Rome, which found in sport - and particularly in football - an emblematic area to express its role of facilitator of social inclusion and its vision of welfare in a complex urban scenario.